Salvia glabrifolia (Lamiaceae), a new species from Hunan, China - Cheng, Ke-Yi; Zhang, Ting; Xie, Chu-Miao; Dai, Jing-Min; Huang, Ming-Hao; Meng, Ying; Tian, Xiang-Rong; Zhang, Dai-Gui; Long, Xiu-Ji; Zhang, Meng-Hua (Phytotaxa, 2024)
Based on molecular and morphological evidence, a new species of Salvia (Lamiaceae), Salvia glabrifolia D.G. Zhang & X.J. Long, from Hunan Province, China, is described and illustrated. Salvia glabrifolia is morphologically similar to S. cavaleriei var. simplicifolia, S. daiguii, and S. cavaleriei var. cavaleriei but is distinct by its glabrous stem, petioles, veins, inflorescence axis, leaf margin repand, and glossy and subleathery leaf texture. Maximum likelihood (ML) analyses of the whole plastome dataset strongly supported S. glabrifolia as a sister to the S. japonica-S. liguliloba clade. Moreover, the chromosome number of S. glabrifolia, 2n = 16, is the same as other species in S. chinensis group.